2020
DOI: 10.1007/s11831-020-09415-3
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Many-Objective Algorithms for Combinatorial Optimization Problems: A Comparative Study

Abstract: Many optimization problems encountered in the real-world have more than two objectives. To address such optimization problems, a number of evolutionary many-objective optimization algorithms were developed recently. In this paper, we tested 18 evolutionary many-objective algorithms against well-known combinatorial optimization problems, including knapsack problem (MOKP), traveling salesman problem (MOTSP), and quadratic assignment problem (mQAP), all up to 10 objectives. Results show that some of the dominance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Zahra et al [30] verified the efficiency of NSGA-II to solve complex combinatorial optimisation problems. Behmanesh et al [31] evalu-ated18 types of evolutionary multiobjective algorithms and confirmed that NSGA-III is effective for optimising NPhard combinatorial optimisation problems.…”
Section: Main Transmission Gearbox (Mtg)mentioning
confidence: 92%
“…Zahra et al [30] verified the efficiency of NSGA-II to solve complex combinatorial optimisation problems. Behmanesh et al [31] evalu-ated18 types of evolutionary multiobjective algorithms and confirmed that NSGA-III is effective for optimising NPhard combinatorial optimisation problems.…”
Section: Main Transmission Gearbox (Mtg)mentioning
confidence: 92%
“…Amongst the various AI-based optimization techniques, MHAs have proven their accuracy and higher computation efficiency when compared with the other conventional optimization techniques [7]. Therefore, MHAs have been adopted to get the optimum solutions for several engineering problems such as power systems problems, as presented in [95][96][97][98][99][100][101][102][103][104]. Besides, depending on the no freelunch theory [105], many researchers have utilized various algorithms for accurate and effective investigation of the polarization characteristics of the PEMFC, as reported in [5,7,16,57].…”
Section: Mhas For Pemfc's Model Parameters Identificationmentioning
confidence: 99%
“…In recent years, several nature-inspired metaheuristic algorithms have emerged and are attracted by many researchers due to nature as a source of inspiration. However, the literature indicates that metaheuristic algorithms are commonly used in different areas like combinatorial t-way testing, but under-appreciated term [5]. In fact, not all the metaheuristics are effective in combinatorial t-way testing, even though some proved to be very effective and thus have been adopted for optimization whilst others are not adopted.…”
Section: Introductionmentioning
confidence: 99%